Adult onset asynchronous multifocal eosinophilic granuloma of bone: an 11-year follow-up. (29th January 2015) - Dallaudière, Benjamin; Kerger, Joseph; Malghem, Jacques; Galant, Christine; Lecouvet, Frederic E
Multifocal eosinophilic granuloma (EG) is a rare observation within the spectrum of histiocytosis X, generally described in children. We report the case of a 33-year-old man with multifocal EG showing an asynchronous evolution of bone lesions during a follow-up of 11 years. We also present the therapeutic approach chosen for this patient and the repeated magnetic resonance imaging (MRI) examinations used to monitor the disease with a final favorable outcome.